1975
DOI: 10.1152/ajplegacy.1975.228.5.1293
|View full text |Cite
|
Sign up to set email alerts
|

Polyuria and imparied ADH release following medial preoptic lesioning in the rat

Abstract: Studies were carried out in the rat to detemine if hypothalamic lesions which caused polydipsia and polyuria had their effect mediated through an alteration of the ability of the neurohypophyseal system to release ADH. Rats with medial preoptic lesions hadincreased water intake while on ad libitum access to water and slightly impaired ability to conserve water following dehydration, but with no impairment of urine-concentrating ability. These were associated with an increase in plasma osmolality both during ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The medial preoptic area is concerned functionally with thermoregulation (Hammel, 1968;Hayward & Baker, 1968), water balance (Hayward & Baker, 1968;Fitzsimons, 1972;van Gemert, Miller, Carey & Moses, 1975), sexual behaviour (Numan, 1974;Pfaff, Daikow, Zigmond & Kow, 1974) and endocrine function, in particular the regulation of pituitary gonadotropin secretion (Halasz, 1969;Cramer & Barraclough, 1973). Until recently there was relatively little data on neuronal connexions between MPOA-AHA and MBH.…”
Section: Introductionmentioning
confidence: 99%
“…The medial preoptic area is concerned functionally with thermoregulation (Hammel, 1968;Hayward & Baker, 1968), water balance (Hayward & Baker, 1968;Fitzsimons, 1972;van Gemert, Miller, Carey & Moses, 1975), sexual behaviour (Numan, 1974;Pfaff, Daikow, Zigmond & Kow, 1974) and endocrine function, in particular the regulation of pituitary gonadotropin secretion (Halasz, 1969;Cramer & Barraclough, 1973). Until recently there was relatively little data on neuronal connexions between MPOA-AHA and MBH.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the vasopressin response to prolonged fluid deprivation can be prevented in rats by producing small lesions in the medial preoptic area of the hypothalamus that do not involve the neurohypophysis. 6 These conclusions are further supported by studies performed about the same time in several patients with hypothalamic pathology and the rare clinical syndrome of adipsic hypernatremia. As originally suggested by indirect studies/, and confirmed recently by direct assay of plasma vasopressin,8.9 some of these patients have a total lack of osmotically mediated vasopressin secretion, but continue to exhibit a normal response to hemodynamic stimuli.…”
Section: Osmoregulationmentioning
confidence: 77%
“…In rats, bilateral N-methyl-D-aspartate lesions produce long-lasting insomnia and increased locomotor activity, but no change in water or food intake (John & Kumar, 1998). Reversible lesions of medial preoptic area, using the anaesthetic agent lidocaine chlorhydrate, cause a transient increase in water intake (Cambiasso & Chiaraviglio, 1992), and radiofrequency electrocoagulative lesions also increase water intake (Van Gemert, Miller, Carey, & Moses, 1975). There are two possible explanations for the discrepancy between the stimulation and lesion data: (a) in the stimulation experiments, AII may have leaked into the third ventricle (although the authors of these studies were fairly certain that this was not the case) or into the median preoptic nucleus, which means that the medial preoptic area is not involved in the thirst system, and the median preoptic nucleus is the essential structure in which signals from the circumventricular organs are integrated; or (b) the lesions did not entirely destroy the subarea of the medial preoptic area that is involved in the generation of thirst.…”
Section: Lesion Studiesmentioning
confidence: 99%